Simulation and Modeling Methodologies, Technologies and Applications 7th International Conference, SIMULTECH 2017 Madrid, Spain, July 26–28, 2017 Revised Selected Papers - Obaidat, Mohammad S.; Ören, Tuncer; Rango, Floriano De (Advances in Intelligent Systems and Computing, 2019)
XIV, 368 p. 202 illus.